A silicon laboratory: chemistry without chemicals - Benites Galbiati, Martín (2013)
The 2013 Nobel Prize in chemistry was awarded to A.Warshel, M.Levitt and M.Karplus for their contribution to the development of hybrid methods for computational chemistry. In this article a brief introduction about computational chemistry methods is presented. This paper will show the order in which the QM/MM (Quantum Mechanics/Molecular Mechanics) methods were developed for the study of macromolecular systems and specially their application in enzymes and biochemistry. Finally, the reach and future prospects of these methods originally developed by A. Warshel, M.Levitt and M. Karplus in the seventies will be discussed.